PERANCANGAN DAN PEMBUATAN SEPEDA LISTRIK PENGISIAN DAYA OTOMATIS DENGAN MENGGUNAKAN MOTOR DC SEBAGAI SUMBER ENERGI ALTERNATOR - ismail, Normansyah (Electrical Network Systems and Sources, 2024)
With the development of technology in two-wheeled motorized vehicles, especially in the drive or transmission system, which is currently dominated by automatic transmissions (Automatic Transmission), slowly, began to replace manual transmissions (Manual Transmission). In terms of motor driving, innovation in the use of alternative energy continues to develop, where the use of an internal combustion engine (BBM) will gradually be replaced by an electric motor as the main driver by utilizing a source of electrical energy stored in the battery. Moving on from the above thought, the author tries to apply the workings of "DC Electric Motors as the Main Source of Bike Driving by Utilizing Battery Energy as an Energy Source", where this electric vehicle or bicycle can be used as an alternative vehicle for short distances, and is environmentally friendly, in an effort to create and Green Energy campaign. In this research, real planning and planning will be carried out, starting from selecting the vehicle model, the type of motor and accumulator used, as well as the vehicle performance and budget planning, selecting the right electric motor based on function, which is a novelty of the technology that will be used. resulting from this research. This electric vehicle is designed to carry a maximum load of 150 kg, with a motor power of 1000 watts 48 volts, a battery capacity of 48 volts 12 Ah, a discharge time of 0.25 minutes (full throtle) with a maximum speed of 60km / hour, or 17m / second. distance of 30 km / charge. Utilization of battery energy as a source of propulsion energy that does not use alternative energy for fossil fuel use, uses environmentally friendly battery energy without air or noise pollution, so it strongly supports environmental protection.